Issues and Perspectives in Decentralisation: Challenges in Democratic Transitions and Local Governance in Global South - Taj, Aamer; Jamal, Waseef; Wali Khan, Shah (The Journal of Humanities & Social Sciences, 2023)
This paper is about decentralisation as a process and the prospects for developing effective local governments in post-colonial societies of Global South. It reviews the issues that hinder the efficacy of decentralised governments and challenges faced in democratic transitions. Discourse in this paper analyses commonalities of issues such as local government representatives’ lack of managerial skills; insufficient delegation of official authority to the local governments; sporadic and ad hoc implementation of reforms; demographic heterogeneity; elite capture of local resources; matters of fiscal autonomy; shortage of public funds; dearth of support from the national and regional governments; and lack of technical support from civil bureaucracy. It is argued that societies in post-colonial states tend to remain apolitical and ‘Not So Civil’ as a consequence of military regimes. Problems pertaining to inter-institutional relationships and corruption in localised governance setup are also discussed as major hurdles.